2021
DOI: 10.2987/21-6967
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding of Mosquitoes from the Pantanos de Centla Biosphere Reserve, Southeastern Mexico

Abstract: Accurate identification of mosquito species is essential to support programs that involve the study of distribution and mosquito control. Numerous mosquito species are difficult to identify based only on morphological characteristics, due to the morphological similarities in different life stages and large numbers of some species that are members of morphologically similar species complexes. In the present study, the mosquitoes collected in the Pantanos de Centla Biosphere Reserve, southeastern Mexico, were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…However, this method is prone to error, especially when identifying mosquitoes belonging to a species complex, as well as isomorphic species, cryptic species, and samples damaged during collection [ 12 ]. Therefore, several more advanced and accurate modern techniques have been used to identify mosquitoes, and these have greatly increased our knowledge and understanding of mosquito vectors [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Culex pseudovishnui , Cx.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this method is prone to error, especially when identifying mosquitoes belonging to a species complex, as well as isomorphic species, cryptic species, and samples damaged during collection [ 12 ]. Therefore, several more advanced and accurate modern techniques have been used to identify mosquitoes, and these have greatly increased our knowledge and understanding of mosquito vectors [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Culex pseudovishnui , Cx.…”
Section: Discussionmentioning
confidence: 99%
“…DNA barcoding is a highly effective molecular technique for the identification of mosquito species that are morphologically similar or indistinguishable [ 21 , 22 , 46 , 47 ]. Our genetic analysis and the ASAP method suggested that DNA barcoding based on COI sequences can be used to distinguish between Cx.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations